Factors contributing to the implementation of data analytics in external auditing / Yeamin Jacky - Yeamin, Jacky (2020)
The objective of the study is to explore the factors effecting the implementation of Data Analytics in Audit process and the impact of those factors on Audit Quality. Two stages of study were performed to achieve the objective of the study, First, this study analysed response letters on the use of Data Analytics (DA) in external auditing submitted by stakeholders of audit services to the International Auditing and Assurance Standards Board (IAASB)’s Data Analytics Working Group (DAWG). Using the Modified IT Audit Model as a framework, this study performs a directed content analysis on all 50 response letters sent to the DAWG. The analysis uncovered some contributing factors which were repeatedly discussed and commented by majority of the stakeholders. Some of the significant factors are namely, challenges in revising or developing new standards, whether DA will be used for substantive testing, test of controls or test of details. Moreover, the effect of DA on Audit quality and audit judgement, and Data reliability, Data security concerns while using DA. The second part of research conducted a survey among auditors based on Malaysia. The study performed an Exploratory Factor Analysis to confirm the validity of the measurements used for factors relating to Audit Profession, Standards (ISAs), Technology, Organizational, Client Factors, Limitation and Challenges and Other Relevant Factors in concern. Based on the initial results of Cronbach alpha, Bartlett test of sphericity (BTOS) and Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMOS) and the factor test, we retained all the attributes with appropriate factor loading. Further descriptive analysis of the findings revealed the current state of using and implementing DA by Malaysian Auditors and audit firms. The analysis suggests a high percentage of auditors and audit firms uses some sort of data analytics but is significantly limited to advance excel and in some areas of audit. The overall findings suggest that although Malaysian practitioners has started developing the use of DA in audit procedures but there are significant limitations and constraint. The findings of this study would be a very critical contributor for standard setters and regulators and as each and every factor has been discussed in different angles, making sure the adopters of DA are well aware of the concerning issues and the benefits in implementing DA in Audit.